Study on ABO & Rhesus Blood Groups in Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2009)
About fifty two thousand admitted patients in different wards & cabins of Rajshahi Medical College Hospital are grouped in the Transfusion Medicine Department for the purpose of blood transfusion during the period of July/ 1997 to June/2000. It is found that out of 51966 patients, 16928 (32.38%) are group B, 16704(32.15%) are group O 13005 (25.02%) are group A, & 5329 (10.25%) are group AB, Among those patients, 50141 (96.51%) are Rh D positive, 1828(3.49%) are negative.   doi: 10.3329/taj.v17i1.3488 TAJ 2004; 17(1) : 38-40